Global Governance: some concerns about authentic democracy addressed - Brock, Gillian (Oñati Socio-Legal Series, 2011)
In this paper I take up a commonly voiced concern about the viability of global governance in general, and cosmopolitan democracy in particular, namely, whether genuine democracy can be achieved at the international level. Some (such as, Will Kymlicka) argue that genuine democracy is only possible within nation-states, because authentic deliberation requires common nationality or identity, which generates the trust and solidarity necessary to sustain deliberation and democracy. Through analysis of the argument and consideration of the requirements of genuine democracy, we can see that these concerns can be addressed. I go on to suggest that the major challenge facing models of global governance is not one concerning lack of common identity, solidarity, or opportunities for authentic deliberation, rather, it lies elsewhere. We can assess global governance arrangements in terms of two main variables, which are sometimes in tension: effectiveness and accountability. We want systems of global governance to incorporate both considerations. Accountability can take the form of democratic procedures but alternative forms of accountability are also possible. Furthermore, a system of governance that both effectively attends to people’s interests and is suitably accountable can certainly claim to have adequate democratic credentials on the “Responsive Democracy” view I discuss.